Copper–Silver Bimetallic Nanowire Arrays for Electrochemical Reduction of Carbon Dioxide - Wang, Yuanxing (Nanomaterials (Basel), 2019)
The electrochemical conversion of carbon dioxide (CO(2)) into gaseous or liquid fuels has the potential to store renewable energies and reduce carbon emissions. Here, we report a three-step synthesis using Cu–Ag bimetallic nanowire arrays as catalysts for electrochemical reduction of CO(2). CuO/Cu(2)O nanowires were first grown by thermal oxidation of copper mesh in ambient air and then reduced by annealing in the presence of hydrogen to form Cu nanowires. Cu–Ag bimetallic nanowires were then produced via galvanic replacement between Cu nanowires and the Ag(+) precursor. The Cu–Ag nanowires showed enhanced catalytic performance over Cu nanowires for electrochemical reduction of CO(2), which could be ascribed to the incorporation of Ag into Cu nanowires leading to suppression of hydrogen evolution. Our work provides a method for tuning the selectivity of copper nanocatalysts for CO(2) reduction by controlling their composition.